Особливості роботи та розрахунків трубопроводів спрягаючої гідротехнічної споруди - Босак, Микола (Видавництво Національного університету «Львівська політехніка», 2001)
In the article the analysis of the reasons of ejections of a mixture of water and air for want of to work of the ganging structures consisting of a tower and closed pipe lines is executed. These processes are studied because of of hydraulic jump and pressure head movement of water in assigning pipe lines.